2004
DOI: 10.3727/000000004772664851
|View full text |Cite
|
Sign up to set email alerts
|

Development and Transplantation of a Mineralized Matrix Formed by Osteoblasts in Vitro for Bone Regeneration

Abstract: The use of extracellular matrix materials as scaffolds for the repair and regeneration of tissues is receiving increased attention. The current study was undertaken to test whether extracellular matrix formed by osteoblasts in vitro could be used as a scaffold for osteoblast transplantation and induce new bone formation in critical size osseous defects in vivo. Human osteoblasts derived from alveolar bone were cultured in six-well plates until confluent and then in mineralization media for a further period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 22 publications
(4 reference statements)
1
40
0
Order By: Relevance
“…It has been well documented that stimulation of osteoblast cell differentiation is characterized mainly by increased expression of ALP, type I collagen, and osteocalcin (Xiao et al, 2004). The action of BMPs is mediated by heterotetrameric serine/ threonine kinase receptors and the downstream transcription factors SMAD1/5/8.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that stimulation of osteoblast cell differentiation is characterized mainly by increased expression of ALP, type I collagen, and osteocalcin (Xiao et al, 2004). The action of BMPs is mediated by heterotetrameric serine/ threonine kinase receptors and the downstream transcription factors SMAD1/5/8.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, osteopontin might not be a mineralization-specific factor. Xiao et al reported that nodules of calcification produced from osteoblasts are detected in the matrix, and that there is a correlation between calcification and the distribution of bone sialoprotein and osteopontin 19) . In addition, the osteopontin secreted from the basolateral surfaces of osteoclasts might act as an autocrine factor by binding to the αVβ3-integrin 20) .…”
Section: Discussionmentioning
confidence: 99%
“…To determine the mechanism underlying the promotion of mineralization by LMW fucoidan, the gene expression of markers of osteoblastic differentiation was studied using cultured 7F2 cells in the absence or presence of LMW fucoidan for 48 h. BMPs are a group of growth factors also known as cytokines and as metabologens, which stimulate osteoblast cell differentiation mainly by increased expression of ALP and osteocalcin (Xiao et al 2004). Our data showed that the expression of BMP-2 significantly increased 2.28 ± 0.06 fold upon treatment with LMW fucoidan at 2 mg/ml (Fig.…”
Section: Effect Of Lmw Fucoidan On Various Gene Expression Levels Of mentioning
confidence: 99%